Preparation method of rubber graft polymer

In the grafting reaction of toughened rubber graft polymer, monomers with different solubility parameters than rubber form an inner graft layer on the surface of the rubber particles, and the distribution of monomers and initiators is controlled, the problems of excessive grafting amount and secondary crosslinking in the rubber particles are solved, and the toughening and mechanical properties are significantly improved.

CN119569963AActive Publication Date: 2025-03-07PETROCHINA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311145423.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-03-07
Estimated Expiration
2043-09-06

AI Technical Summary

Technical Problem

When producing toughened rubber grafting polymers with ‘core-shell’ structure, the amount of grafting in the rubber particles is too large and secondary crosslinking problems, and it is difficult to maintain the graft density of the outer layer of the rubber, affecting the toughening performance.

Method used

By grafting the surface of the rubber particles using monomer 1 with different solubility parameters than rubber at the initial stage of the grafting reaction, an inner graft layer is formed, and monomer 2 with different solubility parameters than inner graft layer is used in the subsequent reaction to ensure that the monomer 2 and the initiator are mainly concentrated on the surface of the rubber particles for polymerization.

Benefits of technology

It effectively reduces the inner grafting and secondary cross-linking of rubber particles, maintains the graft density outside the rubber particles, significantly improves the toughening performance of rubber grafting polymers, and improves the mechanical properties of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004435061760000081
    Figure BDA0004435061760000081
  • Figure BDA0004435061760000091
    Figure BDA0004435061760000091
  • Figure BDA0004435061760000092
    Figure BDA0004435061760000092
Patent Text Reader

Abstract

The invention relates to the technical field of polymer chemical industry, in particular to a preparation method of a rubber graft polymer. The preparation method comprises the following steps: (1) carrying out first reaction on rubber emulsion, a monomer 1, a chain transfer agent 1, an activating agent, an emulsifying agent 1 and an initiator 1 to obtain a first product containing a polymer from the monomer 1; (2) carrying out second reaction on the first product, a monomer 2, a chain transfer agent 2 and an initiator 2 to obtain a second product; and (3) adding an initiator 3 into the second product, and carrying out a third reaction to obtain the rubber graft polymer, wherein the solubility parameter of the monomer 1 is different from that of rubber contained in the rubber emulsion; the solubility parameter of the monomer 2 is different from that of the polymer derived from the monomer 1. According to the technical scheme, grafting and secondary crosslinking in rubber particles in the preparation process are reduced, meanwhile, the grafting density of the outer sides of the rubber particles is not affected, and the toughening performance of the rubber graft polymer can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer chemical industry, and in particular to a method for preparing a rubber grafted polymer. Background Art

[0002] Rubber toughening is the process of blending a small amount of rubber with a rigid polymer to improve the toughness of the material. Both thermoplastic and thermosetting resins can be toughened with rubber. In the process of rubber toughening resin, cavities are first formed inside the rubber particles to weaken the resistance of the particles to deformation, enabling them to induce yielding of the matrix under low stress conditions, allowing the matrix around the hollowed rubber particles to deform in various mechanisms. The larger the rubber particle size, the lower the elastic modulus of the rubber, the easier it is for the rubber particles to cavitate, and the better the mechanical properties of the rubber toughened resin.

[0003] The compatibility of rubber used for toughening resin with resin is often poor. In order to improve the dispersion of rubber in resin, it is necessary to graft a layer of polymer with the same or similar composition as the resin on the surface of the rubber to form a toughened rubber grafted polymer with a "core-shell" structure. When producing such polymers, in order to ensure sufficient grafting amount so that the toughened rubber can be well dispersed in the resin, excessive grafting monomers and initiators are often added. Both will partially enter the rubber particles, causing secondary cross-linking of the rubber and "internal grafting" of the monomers, increasing the elastic modulus of the rubber, increasing the difficulty of rubber cavitation, and reducing the toughening performance of the rubber. Although the method of reducing the amount of initiator and adding monomers and initiators in a continuous or semi-continuous manner can reduce the elastic modulus of the toughened rubber to a certain extent, it will affect the grafting density of the outer layer of the rubber, which is not conducive to the dispersion of the rubber in the resin.

[0004] When producing toughened rubber graft polymers with a "core-shell" structure, how to reduce the grafting and secondary crosslinking inside the rubber particles while ensuring that the external grafting density is not affected and improving the toughening performance of the rubber is an urgent problem to be solved. Therefore, it is of great significance to study a method for rubber graft polymers to solve the above problems. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of excessive grafting amount and secondary crosslinking in rubber particles when producing toughened rubber graft polymers with a "core-shell" structure, while avoiding affecting the grafting density of the rubber outer layer, and to provide a method for preparing a rubber graft polymer.

[0006] In order to achieve the above object, the present invention provides a method for preparing a rubber graft polymer, wherein the method comprises:

[0007] (1) subjecting a rubber latex, a monomer 1, a chain transfer agent 1, an activator, an emulsifier 1 and an initiator 1 to a first reaction to obtain a first product containing a polymer derived from the monomer 1;

[0008] (2) subjecting the first product, monomer 2, chain transfer agent 2 and initiator 2 to a second reaction to obtain a second product;

[0009] (3) adding initiator 3 to the second product to carry out a third reaction to obtain the rubber graft polymer;

[0010] Wherein, the solubility parameter of the monomer 1 is different from that of the rubber contained in the rubber latex;

[0011] Monomer 2 has a different solubility parameter than the polymer from monomer 1.

[0012] The present invention also provides a rubber grafted polymer prepared by the above preparation method, wherein the polymer has a core-shell structure;

[0013] Wherein, the weight ratio of the shell to the core in the polymer is 0.43-0.46:1;

[0014] The impact strength of the polymer is 20-25 kJ / m 2 , the tensile elongation at break is 20-30%.

[0015] Through the above technical scheme, the present invention obtains a polymer with uniform coverage and certain mass transfer resistance to monomers and initiators by grafting on the surface of rubber particles at the initial stage of grafting reaction, and reduces the concentration of shell monomers and initiators forming the external grafting layer, reduces the mass transfer driving force between the grafting layer and the rubber particles, and makes the shell monomers and initiators mainly concentrate on the surface of the rubber particles for polymerization reaction. The grafting efficiency and mechanical properties of the rubber grafted polymer prepared by the present invention are tested, and the results show that it can reduce the grafting and secondary crosslinking inside the rubber particles without affecting the grafting density outside the rubber particles, and can significantly improve the toughening performance of the rubber grafted polymer, break the "rigidity" balance limitation, and comprehensively improve the mechanical properties of the product.

[0016] The invention is applicable to intermittent and continuous emulsion graft polymerization processes, and is particularly applicable to production processes in which graft monomers are added in batches or batch-continuously. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] The specific implementation of the present invention is described in detail below in conjunction with the table. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0019] One aspect of the present invention provides a method for preparing a rubber graft polymer, wherein the method comprises:

[0020] (1) subjecting a rubber latex, a monomer 1, a chain transfer agent 1, an activator, an emulsifier 1 and an initiator 1 to a first reaction to obtain a first product containing a polymer derived from the monomer 1;

[0021] (2) subjecting the first product, monomer 2, chain transfer agent 2 and initiator 2 to a second reaction to obtain a second product;

[0022] (3) adding initiator 3 to the second product to carry out a third reaction to obtain the rubber graft polymer;

[0023] Wherein, the solubility parameter of the monomer 1 is different from that of the rubber contained in the rubber latex;

[0024] Monomer 2 has a different solubility parameter than the polymer from monomer 1.

[0025] The solubility parameter of a substance is defined as the square root of the cohesive energy per unit volume of the substance. It is a parameter value that can characterize the strength of interaction between liquid molecules, between liquid molecules and polymers, and between polymers.

[0026] By calculating the solubility parameter of the polymer and comparing it with the solubility parameter of the solvent, the degree of solubility between the polymer and the solvent can be quantitatively characterized. The closer the solubility parameters of the polymer and the solvent are, the higher the solubility of the polymer; conversely, the greater the difference between the solubility parameters of the polymer and the solvent, the lower the solubility of the polymer.

[0027] According to the preparation method of the present invention, at the initial stage of the grafting reaction, a monomer 1 having a solubility parameter different from that of the rubber is used to obtain a polymer having uniform coverage and a certain mass transfer resistance to the monomer and the initiator on the surface of the rubber particles through grafting, thereby forming an inner grafting layer composed of the polymer from the monomer 1; then, a monomer 2 having a solubility parameter different from that of the polymer from the monomer 1 is added to the reaction system, and the monomer 2 is not easy to pass through the inner grafting layer to reach the rubber surface, so that the monomer 2 and the initiator are mainly concentrated on the surface of the rubber particles for polymerization reaction, thereby reducing the grafting and secondary crosslinking inside the rubber particles without affecting the grafting density outside the rubber particles. In addition, the solubility parameter of the monomer 2 is between the solubility parameter of the rubber and the solubility parameter of the rigid resin to be toughened, which is conducive to promoting the desirability between the toughened rubber and the rigid resin, thereby improving the dispersion of the rubber in the resin.

[0028] According to the present invention, in order to further reduce the driving force of mass transfer between the graft layer and the rubber particles, so that the monomer 2 and the initiator are mainly concentrated on the surface of the rubber particles, while avoiding too low a mass transfer rate of the monomer 2, increasing the copolymerization probability during the mass transfer process, resulting in a decrease in the grafting rate of the toughened rubber and a decrease in the dispersibility of the product in the resin, preferably, in step (2), the mass ratio of the monomer 2 to the initiator 2 is 110-150:1; and the concentration of the initiator 2 is 50-85wt%.

[0029] According to the present invention, in order to improve the compatibility between the toughened rubber and different resins, when modifying the rubber, graft polymerization with different types of monomers 1 and / or monomers 2 is selected. In order to significantly improve the toughening performance of various rubber graft polymers, preferably, in step (2), the mixed solution of the monomer 2 and the chain transfer agent 2 and the initiator 2 can be mixed and added, or they can be added separately.

[0030] According to the present invention, in order to reduce the initiator passing through the inner graft layer, reduce the initiator concentration in the graft layer, avoid secondary crosslinking of the rubber due to the presence of excessive initiator, and improve the mechanical properties of the obtained rubber graft polymer, preferably, in step (2), the mixed solution of the monomer 2 and the chain transfer agent 2 is mixed with the initiator 2 and then added.

[0031] Preferably, the mixed solution of the monomer 2 and the chain transfer agent 2 is mixed with the initiator 2 and then added continuously.

[0032] Preferably, the mixed solution of the monomer 2 and the chain transfer agent 2 is mixed with the initiator 2 and then added in batches.

[0033] According to the present invention, depending on the actual application of the toughened rubber, the rubber will be grafted with different types of monomers 1 and / or monomers 2. In order to make the various rubber graft polymers obtained have higher toughening properties, preferably, the mixture of the monomer 2 and the chain transfer agent 2 and the initiator 2 are added separately. In other words, the mixture of the monomer 2 and the chain transfer agent 2 and the initiator 2 are not mixed but added separately.

[0034] More preferably, the mixed solution of the monomer 2 and the chain transfer agent 2 is added separately from the initiator 2 and simultaneously.

[0035] More preferably, the mixed solution of the monomer 2 and the chain transfer agent 2 is added separately from the initiator 2 and asynchronously.

[0036] Preferably, in order to reduce the concentration of monomers in the latex particles, improve the selectivity of graft polymerization, and avoid excessive monomers and initiators passing through the graft layer to improve the mechanical properties of the product, the monomer addition time can be appropriately extended to avoid too low monomer concentration in the latex particles due to too long addition time and monomers and initiators staying in the graft layer for too long, which may cause monomer copolymerization and reduce product performance. Preferably, in step (2), when adding after mixing, the mixture of monomer 2 and chain transfer agent 2, after mixing with initiator 2, is continuously added for 100-150 minutes.

[0037] Preferably, in step (2), when adding separately, the mixture of the monomer 2 and the chain transfer agent 2 and the initiator 2 are added separately and synchronously for a period of 100-150 minutes.

[0038] According to the preparation method of the present invention, in order to make the obtained rubber graft polymer play a good toughening effect on various resins, preferably, the monomer 1 and the monomer 2 are each independently selected from at least one of acrylonitrile, styrene, α-methylstyrene, methyl methacrylate and methyl acrylate;

[0039] Preferably, the mass ratio of the monomer-1 to the monomer-2 is 1-5:2-10.

[0040] Preferably, the solid content of the rubber latex is 45-60%, and the average particle size of the latex particles contained in the rubber latex is 100-800 nm.

[0041] Further preferably, the rubber latex is selected from at least one of polybutadiene latex, polybutadiene styrene latex and polybutyl acrylate latex.

[0042] According to the present invention, in order to reduce the length of the internal and external grafted molecular chains in the first reaction stage, reduce the elastic modulus, and increase the external grafting density; at the same time, reduce the length of the external grafted chain to avoid the poor compatibility of the grafted polymer and the toughening resin caused by excessive grafting, preferably, the chain transfer agent 1 and the chain transfer agent 2 are each independently selected from tert-dodecyl mercaptan and / or n-dodecyl mercaptan.

[0043] According to the present invention, in order to improve the stability of the reaction system and regulate the amount of monomers entering the latex particles, preferably, the emulsifier 1 and the emulsifier 2 are each independently selected from at least one of potassium disproportionate rosin acid, potassium fatty acid, potassium oleate, sodium butylnaphthalene sulfonate and sodium alkyl sulfate.

[0044] According to the present invention, in order to make the monomer react inside the latex particles, effectively reduce the amount of polymer generated outside the latex particles, and maintain the stability of the polymerization rate during the reaction, preferably, the activator is selected from a reducing sugar-sodium pyrophosphate-ferrous sulfate activation system and / or a sodium formaldehyde sulfoxylate-EDTA-4Na-ferrous sulfate activation system.

[0045] According to the present invention, in order to make the polymerization reaction proceed smoothly and obtain the rubber grafted polymer that meets the requirements, preferably, the initiator 1, initiator 2 and initiator 3 are each independently selected from at least one of cumene hydroperoxide, tert-butyl hydroperoxide, p-menthane hydroperoxide, methylcyclohexane hydroperoxide, p-methylcumene hydroperoxide and tetralin hydroperoxide.

[0046] According to the present invention, in order to effectively control the amount of monomers entering the rubber particles and remaining outside, balance the amount of internal and external grafting of the rubber, and enable the grafted rubber to take into account both the elastic modulus and the dispersion, preferably, in step (1), the mass ratio of the rubber latex, monomer 1, chain transfer agent 1, activator, emulsifier and initiator 1 is 1100-1500: 120-150: 2-5: 50-100: 100-150: 0.5-1.5.

[0047] Preferably, in step (2), the mass ratio of the first product, monomer-2, chain transfer agent-2, and initiator-2 is 1500-2000:0.5-1.5:1:1-3.

[0048] According to the present invention, in order to make the polymerization reaction proceed well and obtain the rubber grafted polymer with greatly improved mechanical properties, preferably, the temperature of the first reaction is 40-60°C and the time is 50-70min;

[0049] And / or, the temperature of the second reaction is 60-78° C., and the time is 100-120 min.

[0050] And / or, the temperature of the third reaction is 75-80°C and the time is 15-30 minutes.

[0051] In some embodiments of the present invention, the temperature of the first reaction is 40°C and the time is 60 min; the temperature of the second reaction is 60°C and the time is 110 min; the temperature of the third reaction is 76°C and the time is 20 min.

[0052] The present invention can reduce the grafting and secondary crosslinking inside the rubber particles without affecting the grafting density outside the rubber particles, can significantly improve the toughening performance of the rubber grafted polymer, break the limitation of the "rigidity" balance, and comprehensively improve the mechanical properties of the product.

[0053] The present invention also provides a rubber grafted polymer prepared by the above preparation method, wherein the polymer has a core-shell structure;

[0054] Wherein, the weight ratio of the shell to the core in the polymer is 0.43-0.46:1;

[0055] The impact strength of the polymer is 20-25 kJ / m 2 , the tensile elongation at break is 20-30%.

[0056] The present invention uses a dynamic light scattering (DLS) particle size analyzer to respectively test the particle size of the raw material PB rubber and the particle size D50 of the obtained rubber grafted polymer after being dispersed in a solvent; uses a dynamic thermomechanical analyzer (DMA) to respectively test the glass transition temperatures of the PB rubber and the rubber grafted polymer in the comparative example and the embodiment, and obtains the glass transition temperature difference ΔTg before and after the PB rubber grafting by calculation. The test result is: the D50 of the rubber grafted polymer after being dispersed in the solvent as a toughening material is ≤2.0 times the particle size of the rubber grafted polymer, indicating that the rubber grafted polymer prepared by the present invention has good compatibility with the resin and has no obvious agglomeration tendency. Therefore, the D50 of the rubber grafted polymer used as a toughening material for resin toughening is closer to the particle size of the grafted rubber particles in a completely dispersed state; the glass transition temperature difference ΔTg before and after the PB rubber grafting represents the change of the elastic modulus before and after the rubber grafting, and the smaller the change of the elastic modulus, the better the rubber toughening.

[0057] The rubber grafted polymer in the present invention has a core-shell structure, wherein the core is a particle used to toughen the rigid polymer, which is usually a polymer with a lower elastic modulus polymerized from a "soft" monomer; the solubility parameter of the polymer constituting the shell structure is between the solubility parameter of the toughened rubber and the solubility parameter of the rigid resin to be toughened, which plays a role in improving the compatibility between the toughened rubber and the rigid resin, and is beneficial to the dispersion of the toughened rubber in the rigid resin.

[0058] The present invention will be described in detail below through examples.

[0059] In the following examples and comparative examples, the evaluation method of the toughened rubber grafting amount and the mechanical properties of the final product is as follows:

[0060] 1. Test method for the grafting amount of toughened rubber monomer and the utilization rate of shell monomer:

[0061] Weigh a certain amount of core-shell polymer powder (taking ABS high-rubber powder as an example) and record it as m g0 , put it in a special test tube and dissolve it in acetone, shake it for 24 hours and separate it in a centrifuge, the centrifugal speed is 10000r / min, and the centrifugal time is 0.5h. After the centrifugal separation, pour out the clear liquid in the test tube, then add an appropriate amount of acetone and repeat the above experiment. The final precipitate is a core-shell polymer. The precipitate is dried to a constant weight and weighed, and the weight is expressed as m g1 Represented by, and based on the content of core polymer in the core-shell polymer powder, the "shell / core" ratio of the core-shell polymer is calculated by formula (1).

[0062]

[0063] in:

[0064] GD%—the percentage of shell polymer to core polymer weight, wt%;

[0065] m g0 —Weigh the weight of the toughened rubber graft powder, g;

[0066] m g1 —The weight of the dried product after centrifugation, g;

[0067] A%—Content of core polymer in toughened rubber graft powder, wt%.

[0068] The shell utilization rate of the shell monomer is calculated by formula (2).

[0069]

[0070] in:

[0071] GE%—the percentage of monomers forming core-shell polymers in the total amount of shell monomers, wt%;

[0072] m g0 —Weigh the weight of the toughened rubber graft powder, g;

[0073] m g1 —The weight of the dried product after centrifugation, g;

[0074] A%—Content of core polymer in toughened rubber graft powder, wt%.

[0075] 2. Test method for rubber particle size and glass transition temperature in products

[0076] (1) Particle size of rubber particles in the product

[0077] Select a suitable solvent to dissolve the test sample, ensuring that the resin phase in the product is completely dissolved while the rubber phase is dispersed without swelling. Add the dissolved sample to the DSL dynamic scattering laser particle size analyzer to test the median particle size D50, μm, of the rubber dispersed in the sample.

[0078] (2) Test of glass transition temperature of rubber phase in product

[0079] The glass transition temperature of the rubber in the product was tested using a dynamic thermomechanical analyzer. A three-point bending fixture was used for the test, and the sample size was 80mm×10mm×4mm. The temperature was scanned at a fixed frequency of 1Hz, with a temperature range of -110 to 30°C and a heating rate of 10°C / min. During the heating process, the peak value of the ratio of the loss modulus to the storage modulus was recorded as the glass transition temperature of the rubber in the product, Tg,°C.

[0080] 3. Preparation of product test specimens and evaluation methods of mechanical properties

[0081] The toughened rubber graft polymer powder and acrylonitrile-styrene copolymer (SAN resin, a commercial product with a grade of 2437 from Jilin Petrochemical Company of PetroChina) were blended and granulated at a weight ratio of 25 / 75, and the mechanical properties of the product were tested according to the method specified in Table 1.

[0082] Table 1

[0083]

[0084]

[0085] For ABS graft polymerization with PB as toughening rubber and AN and St as grafting monomers, the solubility parameter δ of PB is PB =8.4, δ of styrene St =9.3, δ of acrylonitrile AN =10.5, δ of cumene hydroperoxide CHP =10.5, δ of polyacrylonitrile PAN SAN =12.8, δ of polystyrene PS PS =9.05,SAN (75 / 25) The solubility parameter δ SAN =9.6, with the increase of AN% in SAN, the solubility parameter gradually increases.

[0086] Example 1

[0087] (1) adding 3120 kg of polybutadiene (PB) rubber emulsion having a solid content of 57.70% and an average particle size of latex particles of 300 nm, 105.24 kg of monomers of acrylonitrile (AN) and 195.45 kg of styrene (St), 5.811 kg of chain transfer agent tert-dodecyl mercaptan (TDDM), 174 kg of activator (glucose: 2.888 wt %, sodium pyrophosphate: 2.299 wt %, ferrous sulfate: 0.046 wt %, water: 94.767 wt %), 306 kg of emulsifier potassium disproportionate rosin acid solution (solid content: 1.96%), and 1105.86 kg of flushing water into a reaction kettle, heating the contents in the kettle to 40° C., adding 2.232 kg of initiator cumene hydroperoxide (CHP, purity ≥ 80%), and carrying out a first reaction for 60 min, at which time the temperature in the kettle reaches 60° C. to obtain a first product;

[0088] (2) After 234.48 kg of AN, 667.58 kg of St and 3.53 kg of TDDM were mixed, the temperature in the kettle was kept at 60° C., and the obtained mixture was continuously added to the reactor at a constant flow rate within 110 min. At the same time, 8.02 kg of initiator CHP was added to the reactor separately within the same time to carry out the second reaction. After the reaction, the temperature in the kettle rose to 76° C. to obtain the second product;

[0089] (3) The temperature in the kettle was maintained at 76° C., 3.19 kg of initiator CHP was added, and the third reaction was carried out for 20 min to obtain a rubber graft polymer 1.

[0090] Example 2

[0091] The method of Example 1 is followed, except that in step (1), the amount of AN added is 120.28 kg, the amount of St added is 180.41 kg, the amount of TDDM added is 6.127 kg, and the amount of CHP added is 2.353 kg; in step (2), the amount of AN added is 219.44 kg, the amount of St added is 682.61 kg, the amount of TDDM added is 3.46 kg, and the amount of CHP added is 7.86 kg, to obtain a rubber graft polymer 2.

[0092] Example 3

[0093] The method of Example 1 is followed, except that in step (1), the amount of AN added is 126.29 kg, the amount of St added is 234.54 kg, the amount of TDDM added is 6.973 kg, and the amount of CHP added is 2.678 kg; in step (2), the amount of AN added is 213.43 kg, the amount of St added is 628.49 kg, the amount of TDDM added is 3.27 kg, and the amount of CHP added is 7.43 kg, to obtain a rubber grafted polymer 3.

[0094] Example 4

[0095] The method of Example 1 was followed, except that in step (2), 234.48 kg of AN, 667.58 kg of St, 3.53 kg of TDDM and 8.02 kg of initiator CHP were mixed and continuously added to the reactor at a constant flow rate within 110 min to obtain rubber grafted polymer 4.

[0096] Example 5

[0097] The method of Example 1 is followed, except that in step (2), 234.48 kg of AN, 667.58 kg of St, 3.53 kg of TDDM, 8.02 kg of initiator CHP, and 306 kg of emulsifier potassium disproportionate rosin acid solution (solid content of 1.96%) are mixed to form a pre-emulsified monomer, which is then continuously added to the reactor at a constant flow rate within 110 min to obtain a rubber grafted polymer 5.

[0098] Example 6

[0099] The method of Example 1 is followed, except that in step (2), 234.48 kg of AN, 667.58 kg of St and 3.53 kg of TDDM are mixed and then continuously added to the reactor at a constant flow rate within 140 min. At the same time, 8.02 kg of initiator CHP is added to the reactor separately within the same period of time to carry out a second reaction to obtain rubber grafted polymer 6.

[0100] Example 7

[0101] The method of Example 1 is followed, except that in step (2), 234.48 kg of AN, 667.58 kg of St and 3.53 kg of TDDM are mixed and then continuously added to the reactor at a constant flow rate over 170 min. At the same time, 8.02 kg of initiator CHP is added separately to the reactor over the same period of time to carry out a second reaction to obtain rubber grafted polymer 7.

[0102] Example 8

[0103] The method of Example 1 is followed, except that in step (2), after the start of the second reaction, 2.479 kg of initiator CHP is added at a constant flow rate within 0-40 min; 2.625 kg of initiator CHP is added at a constant flow rate within 40-80 min; and 2.078 kg of initiator CHP is added at a constant flow rate within 80-110 min to obtain rubber grafted polymer 8.

[0104] Example 9

[0105] The method of Example 1 is followed, except that in step (2), after the start of the second reaction, a mixture of 90.21 kg of AN, 210.48 kg of St, 1.234 kg of TDDM and 2.804 kg of initiator CHP is continuously added at a constant flow rate within 0-40 min; a mixture of 78.16 kg of AN, 222.53 kg of St, 1.177 kg of TDDM and 2.675 kg of initiator CHP is continuously added at a constant flow rate within 40-80 min; and a mixture of 66.11 kg of AN, 234.57 kg of St, 1.120 kg of TDDM and 2.546 kg of initiator CHP is continuously added at a constant flow rate within 80-110 min to obtain rubber graft polymer 9.

[0106] Example 10

[0107] The method of Example 1 is followed, except that in step (2), after the start of the second reaction, at 0 min, a mixture of 85.26 kg of AN, 242.76 kg of St, 1.28 kg of TDDM and 2.92 kg of CHP is added at one time; at 40 min, a mixture of 85.26 kg of AN, 242.76 kg of St, 1.28 kg of TDDM and 2.92 kg of CHP is added at one time; at 80 min, a mixture of 63.95 kg of AN, 182.07 kg of St, 0.96 kg of TDDM and 2.19 kg of CHP is added at one time to obtain a rubber graft polymer 10.

[0108] Embodiment 11

[0109] The method of Example 10 is followed, except that in step (2), after the start of the second reaction, at 0 min, a mixture of 90.21 kg of AN, 210.48 kg of St, 1.234 kg of TDDM and 2.804 kg of CHP is added at one time; at 40 min, a mixture of 78.16 kg of AN, 222.53 kg of St, 1.177 kg of TDDM and 2.675 kg of CHP is added at one time; at 80 min, a mixture of 66.11 kg of AN, 234.57 kg of St, 1.120 kg of TDDM and 2.546 kg of CHP is added at one time to obtain a rubber graft polymer 11.

[0110] Example 12

[0111] The method of Example 11 is followed, except that in step (2), after the start of the second reaction, at 0 min, the amount of CHP added is 2.383 kg; at 40 min, the amount of CHP added is 2.408 kg; at 80 min, the amount of CHP added is 2.419 kg, to obtain a rubber grafted polymer 12.

[0112] Example 13

[0113] The method of Example 1 is followed, except that in step (1), 180.41 g of methyl acrylate is added instead of 105.24 kg of AN and 195.45 kg of St; the amount of TDDM added is 3.002 kg, and the amount of CHP added is 1.153 kg; in step (2), the amount of AN added is 286.25 kg, the amount of St added is 736.08 kg, the amount of TDDM added is 4.099 kg, and the amount of CHP added is 9.315 kg, to obtain a rubber graft polymer 13.

[0114] Comparative Example 1

[0115] The method of Example 1 is followed, except that in step (1), the amount of AN added is 84.25 kg, the amount of St added is 216.43 kg, the amount of TDDM added is 5.37 kg, and the amount of CHP added is 2.06 kg; in step (2), the amount of AN added is 255.47 kg, the amount of St added is 646.58 kg, the amount of TDDM added is 3.63 kg, and the amount of CHP added is 8.25 kg, to obtain a rubber grafted polymer 14.

[0116] Comparative Example 2

[0117] The method of Example 1 was followed, except that in step (1), the amount of AN added was 84.25 kg, the amount of St added was 216.43 kg, the amount of TDDM added was 5.37 kg, and the amount of CHP added was 2.06 kg; in step (2), after the second reaction started, at 0 min, 92.9 kg of AN, 325.12 kg of St, 1.32 kg of TDDM, and 3.00 kg of CHP were added at once; at 40 min, 92.9 kg of AN, 325.12 kg of St, 1.32 kg of TDDM, and 3.00 kg of CHP were added at once; at 80 min, 69.67 kg of AN, 176.34 kg of St, 0.99 kg of TDDM, and 2.25 kg of CHP were added at once. Rubber grafted polymer 15 was obtained.

[0118] Test Case

[0119] The polymer emulsions obtained in the above examples and comparative examples were demulsified using an acidic coagulant (98% concentrated sulfuric acid), washed, dehydrated and dried to obtain powder of the rubber grafted polymer. The grafting amounts of the obtained rubber grafted polymer were obtained by formulas (1) and (2): GD% and GE%, respectively. The results are shown in Table 2:

[0120] Table 2

[0121]

[0122] The particle size of the raw material PB rubber in the comparative example and the embodiment and the particle size D50 of the obtained rubber grafted polymer after being dispersed by the solvent were respectively measured by a dynamic light scattering (DLS) particle size analyzer; the glass transition temperature of the PB rubber and the rubber grafted polymer in the comparative example and the embodiment were respectively measured by a dynamic thermodynamic analyzer (DMA), and the glass transition temperature difference ΔTg before and after the PB rubber grafting was obtained by calculation. The results are shown in Table 3:

[0123] Table 3

[0124]

[0125] The mechanical properties of the product were tested according to the method specified in Table 1. The results are shown in Table 4:

[0126] Table 4

[0127]

[0128]

[0129] It can be seen from Tables 2 and 3 that by adopting the method proposed in the present application, by adjusting the monomer composition in each stage of the reaction, the amount of initiator used and the monomer addition time in the second reaction stage, a layer of polymer having a certain mass transfer resistance to the monomer and the initiator is covered on the rubber particles, thereby reducing the mass transfer of the monomer and the initiator in the rubber particles while ensuring that the outer layer grafting density is not affected.

[0130] Comparing Comparative Example 1 and Examples 1-3, as the AN% of the first reaction monomer increases, the PB grafting rate (GD) and the grafting efficiency (GE) of the monomers decrease slightly. Compared with increasing the AN% of the first reaction monomer, increasing the amount of the first reaction monomer has a relatively small effect on the grafting rate. After adjusting the AN% and amount of the first reaction monomer, the glass transition temperature drop ΔTg of the rubber before and after grafting is reduced from 4.0°C to 2.2°C, and the median particle size D of the rubber in the product is 50 Increasing from 448nm to 481nm, the mechanical properties of the product have been improved, the impact strength has been increased from 21.18kJ / ㎡ to 22.80kJ / ㎡, the tensile elongation at break has been increased from 18.5% to 22.5%, and other mechanical performance indicators have also been improved to varying degrees, and the toughness of the product has been significantly improved.

[0131] Comparing Examples 1, 4 and 5, compared with adding CHP alone, mixing CHP with monomers or pre-emulsifying both before adding to the reaction system can reduce the rate at which CHP enters the latex particles, reduce the concentration of CHP in the grafting layer, avoid secondary crosslinking of PB due to the presence of excessive CHP, and reduce the glass transition temperature difference ΔTg before and after rubber grafting from 2.2-2.4°C to 1.1-1.3°C. Adjusting the CHP addition method will not have an adverse effect on the PB grafting rate and the monomer grafting efficiency. The median particle size D of the rubber particles in the product is 50 Maintained at 477-480nm; Due to the reduction of the glass transition temperature of rubber, the impact strength of the product is improved. After the initiator and monomer are mixed and pre-emulsified and then added continuously, the impact strength can reach 23.83kJ / ㎡, the tensile elongation at break can reach 25.4%, and the tensile strength can reach 43.5MPa at the same time, and the product mechanics are significantly improved.

[0132] Comparing Examples 1, 6 and 7, the monomer concentration in the latex particles can be reduced by extending the monomer dropwise addition time. On the one hand, a high PB / monomer ratio can improve the selectivity of graft polymerization, and on the other hand, it can prevent excessive monomers and CHP from entering and breaking through the inner graft layer. The glass transition temperature difference ΔTg before and after rubber grafting is further reduced from 2.4°C to 0.8°C, thereby improving the mechanical properties of the product. However, if the dropwise addition time is too long, the monomer concentration in the latex particles is too low, and the monomer and CHP stay in the graft layer for too long, which will cause the monomer to copolymerize, which will reduce the PB grafting rate and make the median particle size D of the rubber particles in the product 50When increasing from 462nm to 520nm, product performance has declined.

[0133] Comparing Examples 1 and 8, CHP is added in stages during the second reaction. In the early stage of the second reaction, the graft layer is relatively thin, and the monomer and initiator can still quickly pass through the graft layer to reach the surface of the latex particles and penetrate into the latex particles. Appropriately reducing the amount of initiator can avoid excessive CHP entering the latex particles due to the thin graft layer or poor uniformity of the first reaction; as the second reaction proceeds, the thickness of the PB outer layer polymer gradually increases, and the monomer and initiator need longer time to reach the PB surface. At this time, it is necessary to appropriately increase the amount of CHP to shorten the time for CHP to reach PB, so as to avoid the copolymerization of the initiator monomer due to the long residence time of CHP in the outer graft layer, which significantly affects the PB grafting rate. Compared with Example 1, the PB grafting rate of Example 8 is slightly lower, but the glass transition temperature difference ΔTg before and after rubber grafting is equal to 1.0°C, and the median particle size D50 of the rubber particles in the product is still less than 500nm, and the mechanical properties of the product are good.

[0134] Comparing Examples 1 and 9, without changing the total amount of AN and St, different AN% of grafting monomers are used in each period of the second reaction. As the reaction proceeds, the AN% of the added grafting monomers gradually decreases, and the amounts of CHP and TDDM are adjusted according to the molar amount of the grafting monomers. At the end of the first reaction, some exposure will inevitably exist on the surface of PB; the use of high AN% monomers at the beginning of the second reaction can "repair" to a certain extent, avoiding excessive monomers and initiators from entering the PB, so that the glass transition temperature difference ΔTg before and after rubber grafting in the final product is not higher than 1.0°C. As the reaction proceeds, a grafting layer with a gradually decreasing AN% will be formed on the outside of PB, resulting in a gradual increase in the time required for the subsequently added monomers to reach the surface of PB, a decrease in the PB grafting rate and the monomer grafting efficiency, and a median particle size D50 of the rubber particles in the product exceeding 550nm. Due to the poor grafting effect, a small amount of grafted rubber particles agglomerated to form a small amount of rubber agglomerated particles with a particle size of 0.8-1.5μm. These micro-agglomerated particles can make the 400-600nm rubber particles form a bimodal distribution of rubber particle size, and utilize the synergistic toughening mechanism of large and small particle sizes to improve the product's impact strength and tensile elongation at break.

[0135] Comparing Comparative Example 2 with Example 10, when the ABS graft polymerization is carried out by the staged feeding method, by increasing the AN% of the first feeding monomer, the mechanical properties of the product can also be improved while increasing the PB grafting rate and the monomer grafting efficiency.

[0136] Comparing Examples 10 and 11, in the second reaction stage, when the ABS graft polymerization is carried out by adopting the segmented batch feeding method, by adjusting the monomer composition in each period of the second reaction stage, and adjusting the amount of initiator and chain transfer agent in proportion according to the molar amount of the monomer, not only the coverage of the grafted polymer outside the PB can be improved, but also excessive monomers can be prevented from entering the PB, and the glass transition temperature difference ΔTg before and after the rubber grafting in the product is less than 1.5°C. However, a grafting layer with a gradually decreasing AN% will be formed on the outside of the PB, resulting in a gradual extension of the time required for the subsequently added monomers to reach the PB surface, a decrease in the PB grafting rate and the monomer grafting efficiency, and a rubber particle size D in the product. 50 There is a slight increase, but the product's impact strength and tensile elongation at break have been improved.

[0137] Comparing Examples 11 and 12, when ABS grafting polymerization is carried out by adopting the segmented batch feeding method, by adjusting the second reaction stage, while reducing the AN% of the monomer added in each period, the amount of initiator is further gradually reduced. It can further prevent excessive initiator from entering the PB, and the glass transition temperature difference ΔTg before and after rubber grafting is reduced to 1.2°C. However, due to the reduction in the amount of initiator outside the PB, the grafting rate and monomer grafting efficiency are reduced, and the median particle size D50 of the rubber particles in the product reaches 575nm. At the same time, during the blending process of the grafted powder with SAN, the rubber particles undergo a certain degree of agglomeration, forming a small amount of micro-agglomerated particles that can form a synergistic toughening effect of large and small particle sizes with rubber particles of normal particle size, thereby improving the product impact strength and tensile elongation at break.

[0138] Comparing Comparative Example 1 and Example 13, by adding methyl methacrylate with a higher solubility parameter in the first reaction, the grafting rate of PB is slightly reduced, the glass transition temperature difference ΔTg before and after rubber grafting is reduced to 1.0°C, and the rubber particle size D50 also reaches 530nm. However, the mechanical properties of the product are improved, the impact strength is increased from 21.18 kJ / ㎡ to 22.25 kJ / ㎡, and the tensile elongation at break is increased from 18.5% to 21.5%. Other mechanical performance indicators are also improved to varying degrees, and the toughness of the product is significantly improved.

[0139] It can be seen from the above embodiments and comparative examples that the present invention can reduce the grafting and secondary crosslinking inside the rubber particles and lower the glass transition temperature of the rubber phase without affecting the grafting density outside the rubber particles, so that the rubber phase can maintain good dispersion in the rigid polymer, at least 50% of the rubber particles can exist in a non-agglomerated state, and a small amount of rubber particles that are agglomerated due to the reduced grafting rate can also play a bimodal synergistic toughening effect with the completely dispersed rubber particles, which can significantly improve the toughening performance of the ABS grafted powder, break the "rigidity" balance limitation, and comprehensively improve the mechanical properties of the product.

[0140] The invention is applicable to intermittent and continuous emulsion graft polymerization processes, and is particularly applicable to production processes in which graft monomers are added in batches or batch / continuously.

[0141] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a rubber graft polymer, characterized in that: The method comprises: (1) subjecting a rubber latex, a monomer 1, a chain transfer agent 1, an activator, an emulsifier 1 and an initiator 1 to a first reaction to obtain a first product containing a polymer derived from the monomer 1; (2) subjecting the first product, monomer 2, chain transfer agent 2 and initiator 2 to a second reaction to obtain a second product; (3) adding initiator 3 to the second product to carry out a third reaction to obtain the rubber graft polymer; Wherein, the solubility parameter of the monomer 1 is different from that of the rubber contained in the rubber latex; Monomer 2 has a different solubility parameter than the polymer from monomer 1.

2. The preparation method according to claim 1, wherein In step (2), the mass ratio of monomer 2 to initiator 2 is 110-150:1; the concentration of initiator 2 is 50-85wt%.

3. The preparation method according to claim 1 or 2, wherein In step (2), the mixed solution of the monomer 2 and the chain transfer agent 2 is mixed with the initiator 2 and then added; Alternatively, the mixed solution of the monomer 2 and the chain transfer agent 2 and the initiator 2 are added separately.

4. The preparation method according to claim 3, wherein In step (2), when adding after mixing, the mixed solution of the monomer 2 and the chain transfer agent 2 is mixed with the initiator 2 and then added in batches or continuously; And / or, when adding separately, the mixed solution of the monomer 2 and the chain transfer agent 2 is added synchronously with the initiator 2, or the mixed solution of the monomer 2 and the chain transfer agent 2 is added asynchronously with the initiator 2.

5. The preparation method according to claim 3 or 4, wherein In step (2), during the post-mixing addition, the mixed solution of the monomer 2 and the chain transfer agent 2, the initiator 2 and the emulsifier 2 are mixed.

6. The preparation method according to claim 4, wherein When adding after mixing, the continuous adding time is 100-150min; And / or, when adding separately, the time of adding simultaneously is 100-150 minutes.

7. The preparation method according to any one of claims 1 to 3, wherein: The monomer 1 and the monomer 2 are each independently selected from at least one of acrylonitrile, styrene, α-methylstyrene, methyl methacrylate and methyl acrylate; And / or, the mass ratio of monomer-1 to monomer-2 is 1-5:2-10.

8. The preparation method according to any one of claims 1 to 7, wherein: The solid content of the rubber latex is 45-60%, and the average particle size of the latex particles contained in the rubber latex is 100-800nm; Wherein, the rubber latex is selected from at least one of polybutadiene latex, polybutadiene styrene latex and polybutyl acrylate latex.

9. The preparation method according to any one of claims 1 to 8, wherein: The chain transfer agent 1 and the chain transfer agent 2 are each independently selected from tert-dodecyl mercaptan and / or n-dodecyl mercaptan; And / or, the emulsifier 1 is at least one selected from potassium disproportionate rosin acid, potassium fatty acid, potassium oleate, sodium butylnaphthalene sulfonate and sodium alkyl sulfate; And / or, the activator is selected from a reducing sugar-sodium pyrophosphate-ferrous sulfate activation system and / or a sodium formaldehyde sulfoxylate-EDTA-4Na-ferrous sulfate activation system; And / or, the initiator 1, initiator 2 and initiator 3 are each independently selected from at least one of cumene hydroperoxide, tert-butyl hydroperoxide, p-menthane hydroperoxide, methylcyclohexane hydroperoxide, p-methylcumene hydroperoxide and tetralin hydroperoxide.

10. The preparation method according to claim 5, wherein: The emulsifier 2 is selected from at least one of potassium disproportionate rosin acid, potassium fatty acid, potassium oleate, sodium butylnaphthalene sulfonate and sodium alkyl sulfate.

11. The preparation method according to any one of claims 1 to 10, wherein: In step (1), the mass ratio of the rubber latex, monomer 1, chain transfer agent 1, activator, emulsifier 1 and initiator 1 is 1100-1500:120-150:2-5:50-100:100-150:1; And / or, in step (2), the mass ratio of the first product, monomer 2, chain transfer agent 2, and initiator 2 is 1500-2000:200-300:1:1-3.

12. The preparation method according to any one of claims 1 to 11, wherein: The temperature of the first reaction is 40-60°C and the time is 50-70min; And / or, the temperature of the second reaction is 60-78°C and the time is 100-120min; And / or, the temperature of the third reaction is 78-80° C. and the time is 15-30 min.

Citation Information

Patent Citations

  • Method for preparing rubber reinforced graft copolymer and rubber reinforced graft copolymer prepared thereby

    CN105189587A

  • Methyl methacrylate-acrylonitrile-butadiene-styrene (MABS) polymer and preparation method thereof

    CN110144030A

  • Polybutadiene grafted copolymer, and preparation method and application thereof

    CN111116832A

  • Method for preparing graft copolymer with minimized volatile organic compound emissions

    KR1020090062488A

  • Method for preparing ABS graft copolymer

    KR1020160054742A